A Framework to Consider Soil Ecosystem Services in Territorial Planning - Fossey, Maxime; Angers, Denis; Bustany, Céline; Cudennec, Christophe; Durand, Patrick; Gascuel-Odoux, Chantal; Jaffrezic, Anne; Pérès, Guénola; Besse, Christelle; Walter, Christian (Frontiers in Environmental Science, 2020)
As a critical interface in the environment, soils can provide a wide range of ecosystem services (ES). However, while there is growing demand to assess soil ES from agricultural systems, considering them in land management strategies remains a challenge. Indeed, because of the difficulty in relating soil properties to ES, soil ES are still not fully considered in the territorial planning decision process. Through a comprehensive approach based on soil processes, an assessment framework is proposed to make soil ES understandable and usable by actors of territorial planning. This assessment framework is based on a conceptual model that is then developed into an operational framework. The conceptual model, which is supported by a literature review, relates agricultural soil ES to common socio-economic development challenges. The operational framework is based on the development of soil ES modelling and enables comparison of soil management options, which provides information to help choose among planning scenarios. This soil ES assessment framework, relating soil science to territorial governance, should improve integration of soil ES into decision making in a territorial planning context and support sustainable socio-economic development.